The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4067/s0717-95022015000200018
|View full text |Cite
|
Sign up to set email alerts
|

Expression of VEGF and CD68 in the Placenta of Gestational Diabetic Mothers (Immunohistochemistry and Ultrastructural Study)

Abstract: SUMMARY: Placental angiogenesis, is essential for embryonic and fetal development. In this study, 18 gestational diabetes mellitus and 22 control pregnancies were included. Gestational diabetes mellitus (GDM) groups compared to the control group significantly higher values were detected (p<0.01). The following histological results were assessed; villous immaturity, chorangiosis, presence of, sncytial knots,mononuclear cell infiltration ischemia and fibrinoid necrosis. To evaluate and compare the placental hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Although it would be sensible to assume the involvement of GDM-CMSCs in hypervascularisation, CMSCs derived from GDM placenta did not show an increase in vasculogenesis-associated gene expression or angiogenesis pathway activity, suggesting that CMSCs may not contribute to placental hypervascularisation in GDM. On the contrary, immunohistochemistry staining of increased VEGF protein in cytotrophoblast and syncytiotrophoblast cells of GDM chronic villi [38,39], flow cytometry identifying elevated levels of VEGF receptors on endothelial progenitor cells from GDM women [40], and increased cytokine production from Hofbauer and placental cells [41] were all associated with enhanced angiogenesis and vasculogenesis in GDM. Various cell types in GDM placenta contribute to hypervascularisation while reduced angiogenic ability in GDM-CMSCs might represent a compensatory response to counteract dysregulated angiogenesis and vascularisation or be implicated in vascular function defects of GDM placenta.…”
Section: Discussionmentioning
confidence: 93%
“…Although it would be sensible to assume the involvement of GDM-CMSCs in hypervascularisation, CMSCs derived from GDM placenta did not show an increase in vasculogenesis-associated gene expression or angiogenesis pathway activity, suggesting that CMSCs may not contribute to placental hypervascularisation in GDM. On the contrary, immunohistochemistry staining of increased VEGF protein in cytotrophoblast and syncytiotrophoblast cells of GDM chronic villi [38,39], flow cytometry identifying elevated levels of VEGF receptors on endothelial progenitor cells from GDM women [40], and increased cytokine production from Hofbauer and placental cells [41] were all associated with enhanced angiogenesis and vasculogenesis in GDM. Various cell types in GDM placenta contribute to hypervascularisation while reduced angiogenic ability in GDM-CMSCs might represent a compensatory response to counteract dysregulated angiogenesis and vascularisation or be implicated in vascular function defects of GDM placenta.…”
Section: Discussionmentioning
confidence: 93%
“…They did not find any mitotic activity of the Hofbauer cells, because the Ki-67 marker for cellular multiplication was negative in all the specimens examined. Yavuz et al (2015) studied VEGF and CD68 expression immunohistochemically in the placenta of mothers with GDM. They verified that the expression of VEGF and its receptors increased in the placental chorionic villi mainly in GDM, whereas in the nondiabetic villi a weak VEGF expression was detected.…”
Section: Methodsmentioning
confidence: 99%
“…78 Studies reported that hyperglycaemia, hyperinsulinaemia, dyslipidaemia and hypoxic uterine environment are the causes of VEGF and fibroblast growth factor 2 overexpression. 75,[79][80][81] When VEGF binds to its receptor, it induces the self-phosphorylation of cadherin, which causes interruptions in the adherens junctions of endothelial cells, leading to increased vascular permeability. 81,82 Although data on angiogenic factors in GDM are limited, there are recent studies suggesting that VEGF overexpression would be secondary to an increase in the angiogenic placental growth factor, which increases cell sensitivity to VEGF.…”
Section: Placental Vascular Alterationsmentioning
confidence: 99%